2006
DOI: 10.14310/horm.2002.11164
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Osteoporosis in Men: Association or Casual Link?

Abstract: The longer life expectancy of women than that of men and, therefore, the longer exposure to fracture risk has, at least partially, led to neglect of osteoporosis in men. Recently, unipolar depression, which is 2 times more frequent in women than in men, has been linked to osteoporosis. However, it is quite possible that this diagnosis may escape detection in men because of a different behavioral phenotype between the genders. A potential mechanism of bone loss in depression has been proposed, involving concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 64 publications
0
21
1
Order By: Relevance
“…Nevertheless, our attempts to assess the specific role of central IL-1 in the depression-induced bone loss were unsuccessful because IL1rKO mice were resistant to CMS, namely, they did not exhibit CMS-induced decreases in depressive or skeletal parameters. In addition, it has been recently suggested that depression-induced elevations in the serum levels of another cytokine, IL-6, comprise a risk factor for osteoporosis (25,32). However, this suggestion is not supported by the present findings, which suggest that an increase in blood IL-6 levels is not critically involved in CMS-induced bone loss.…”
Section: Discussioncontrasting
confidence: 95%
“…Nevertheless, our attempts to assess the specific role of central IL-1 in the depression-induced bone loss were unsuccessful because IL1rKO mice were resistant to CMS, namely, they did not exhibit CMS-induced decreases in depressive or skeletal parameters. In addition, it has been recently suggested that depression-induced elevations in the serum levels of another cytokine, IL-6, comprise a risk factor for osteoporosis (25,32). However, this suggestion is not supported by the present findings, which suggest that an increase in blood IL-6 levels is not critically involved in CMS-induced bone loss.…”
Section: Discussioncontrasting
confidence: 95%
“…However, this association in postmenopausal women may be masked by other factors contributing to low BMD, such as estrogen depletion, reduced physical activity, and drug treatments [32]. There were several studies concerning the relation between osteoporosis and depression in men [35,36]. In a population study of 80 depression patients, including 27 men, the spine BMD was 15% lower than in the control subjects [37].…”
Section: Relationship Between Chronic Psychological Stress and Osteopmentioning
confidence: 99%
“…The other approach, that depression is the causal process, claims that most studies demonstrate an association of depression with low BMD rather than with increased fracture rate. That depression is the causal attribute has been further proposed based on the wellestablished depression-induced increases in glucocorticoids and norepinephrine [10], agents also known to suppress bone formation and bone mass [11,12].…”
Section: Causal Relationship Between Depression and Bone Lossmentioning
confidence: 99%